Endocannabinoid modulation of allergic responses: Focus on the control of FcεRI-mediated mast cell activation - Rubi Monserrat Osorio-Perez; Gabriela Rodríguez-Manzo; Zyanya P. Espinosa-Riquer; Silvia L. Cruz; Claudia González-Espinosa (European Journal of Cell Biology, 2023)
Allergic reactions are highly prevalent pathologies initiated by the production of IgE antibodies against harmless antigens (allergens) and the activation of the high-affinity IgE receptor (FcεRI) expressed in the surface of basophils and mast cells (MCs). Research on the mechanisms of negative control of those exacerbated inflammatory reactions has been intense in recent years. Endocannabinoids (eCBs) show important regulatory effects on MC-mediated immune responses, mainly inhibiting the production of pro-inflammatory mediators. However, the description of the molecular mechanisms involved in eCB control of MC activation is far from complete. In this review, we aim to summarize the available information regarding the role of eCBs in the modulation of FcεRI-dependent activation of that cell type, emphasizing the description of the eCB system and the existence of some of its elements in MCs. Unique characteristics of the eCB system and cannabinoid receptors (CBRs) localization and signaling in MCs are mentioned. The described and putative points of cross-talk between CBRs and FcεRI signaling cascades are also presented. Finally, we discuss some important considerations in the study of the effects of eCBs in MCs and the perspectives in the field.